Elucidating the role of the SATB1 gene in breast cancer carcinogenesis in the presence or absence of tocotrienol-rich fraction : evidence from a syngeneic mouse model of breast cancer - Sitti Rahma Abdul Hafid; Ammu Kutty Radhakrishnan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Tocotrienols are reported to possess anticancer activities. Recently we showed that the anticancer effects of tocotrienolrich fraction (TRF) may be through inhibition of the special AT-rich sequence-binding protein 1 (SATB1) gene in a syngeneic mouse model of breast cancer (BC). The present study aims to further explore the role of the SATB1 gene in murine BC cells. The expression of the SATB1 gene in the 4T1 murine BC cells was partially knocked down (SATB1-4T1) using the short hairpin RNA (shRNA) technology and these cells were injected into the mammary pads of mice. Control groups were injected with wild-type 4T1 (WT 4T1) cells. When the tumour was palpable, half of the mice in both groups were fed daily with 1 mg TRF and received intraperitoneal injections of dendritic cells pulsed with tumour lysate (DC+TL) once a week for three weeks. The tumour incidence in mice injected with the SATB1-4T1 cells was reduced (p<0.05) and this effect was independent of TRF supplementation. However, in mice injected with WT-4T1, there was inhibition of tumour growth (p<0.05) only in the group fed with TRF. In addition, the expression of S1004A and mutant P53 genes were suppressed in tumours from animals that were injected with the SATB1-4T1 cells, irrespective of TRF supplementation; which was also observed in tumours from mice injected with WT 4T1 cells and fed with TRF. These findings suggest that TRF may work through the SATB1 pathway.